2018
DOI: 10.1037/vio0000086
|View full text |Cite
|
Sign up to set email alerts
|

Cross-informant agreement on mental health outcomes in children with maltreatment histories: A systematic review.

Abstract: Objective: This systematic review and meta-analysis examined cross-informant agreement concerning mental health outcomes for maltreated children. This study provides important information to individuals working with maltreated children (e.g., clinicians, child welfare practitioners) who must make critical decisions related to safety, mental health, and permanency. Method: We retrieved 29 studies that collected mental health data for maltreated children using standardized instruments. We were able to examine 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…They are positively associated with Factor 2 and all the health problems indicators. These relations were predicted by previous empirical research (Daversa, 2010;Gao et al, 2010;Farrington, 2006;Repetti et al, 2002;Romano, Weegar, Babchishin, & Saini, 2018). Furthermore, the data showed that Factor 2, especially the Lifestyle features, partially mediate the link between family dysfunctions and health status: the result which is in line with previous data on the role of impulsiveness and disinhibition in diminished health (Lovello, 2013).…”
Section: Family Dysfunctions Psychopathy and Health Problemssupporting
confidence: 89%
“…They are positively associated with Factor 2 and all the health problems indicators. These relations were predicted by previous empirical research (Daversa, 2010;Gao et al, 2010;Farrington, 2006;Repetti et al, 2002;Romano, Weegar, Babchishin, & Saini, 2018). Furthermore, the data showed that Factor 2, especially the Lifestyle features, partially mediate the link between family dysfunctions and health status: the result which is in line with previous data on the role of impulsiveness and disinhibition in diminished health (Lovello, 2013).…”
Section: Family Dysfunctions Psychopathy and Health Problemssupporting
confidence: 89%
“…Work on intersubjectivity effects may also inform interpretations of subjective reports within specialty areas of Clinical Psychology, such as Forensic Psychology. In particular, researchers and practitioners often encounter great difficulty with interpreting divergence among reports about child mental health taken for the purposes of child maltreatment evaluations (for a review, see Romano, Weegar, Babchishin, & Saini, 2018). Indeed, in these evaluations, divergence between reports could arise, for instance, because of extraneous factors such as a motivation on the part of an informant to report socially desirable behaviors in an effort to influence a key outcome (e.g., custody placement).…”
Section: Clinical and Developmental Psychologymentioning
confidence: 99%
“…Further research is also needed to explore these results with comparisons of women not reporting domestic violence. Children's impact was measured indirectly by mothers rather than through direct observation and this may influence these results given the previously reported differences in cross-informant consistency (Romano, Weegar, Babchishin, & Saini, 2018). Also, not all participants answered every question, and because some questions in the survey allowed for entry of free text, some responses were uninterpretable (e.g., "Canadian" as a race) and therefore some of the demographic responses do not sum to the total sample.…”
Section: Limitationsmentioning
confidence: 99%